Population of Thrips sp. on the Integrated Pest Management and Conventional farming on Chilli (Capsicum annuum L.) at Bayem Village, Sub-District Kasembon, Malang - Bachtiar Rachmad Sugiyono; Gatot Mudjiono; Rina Rachmawati (Graduate Program, 2017)
This research aimed to find out an abundance of Thrips sp. population on Integrated Pest Management (IPM) and conventional farming at chilli plantation. The research was conducted on August until November 2012 at the Bayem Village, Sub-distric Kasembon, Malang, East Java and Entomology Laboratory, Departement of Plant Protection, Agriculture Faculty, Brawijaya University. The methods to determine abundance population Thrips sp. was using quadrant with 4 plants samples in 1 beds were taken. The observation was using 16 plants, on the each treatment of IPM and conventional farming. The result showed that the population of Thrips sp. (nymph) on IPM and conventional was not significantly different, while the population of Thrips sp. (adult) in the IPM treatment was significantly higher compared to conventional. Plant height on IPM treatment was higher than conventional treatment. The statistical analysis on Thrips sp. attacks indicated, that the intensity of damage on IPM treatment (0.16 %) and conventional treatment (0,14 %) were not significantly different. The yield of chilli on the IPM (31%) was significantly higher than compared to conventional treatment. Chilli cultivation costs on IPM was higher (2.5%) rather than the conventional. The yield of chilli plant per hectare on IPM had advantage higher (37%) than conventional. The calculation of the BCR at the IPM was higher (27%) than the conventional farming.Key words: Abundance, analysis of farming, IPM, Thrips sp.